Methods of child psychology and their practical applications in reborn Poland in Aniela Szycówna’s view - IZDEBSKI, PAWEŁ (Studia Psychologica: Theoria et praxis, 2016)
The purpose of this short article is to present the works of Aniela Szycówna, an outstanding researcher of children’s minds. The article describes methods used by her and their practical applications. Szycówna is one of the pioneers of Polish developmental psychology and empirical pedagogy based on the research in children’s development. Her interests in the problems of child development, education and the work of teachers led to significant research attainments, which influenced the way of thinking of the whole generation of teachers working in reborn Poland.